Gaze Sensitive Theta Oscillations in Young Autistic Children - Pérez Rodríguez, Catalina (My University, 2025)
The ability to detect and process the gaze of others is relevant for human social interaction. Typically developing children show an attentional bias towards direct gaze (i.e., gaze directed towards the observer) from an early age. In children diagnosed with autism spectrum disorder, however, this bias can be altered and manifested often as a reduced use of eye contact. The neural mechanisms behind atypical eye contact in autism remain unclear. Different models have been proposed and tested using different methods from which the study of ERP components –such as N170– being the most reported. However, data obtained from young children are underreported. The analysis of ERPs in this population is complicated due to the high number of stimuli repetitions needed to visualize components. In this context, the analysis of oscillatory rhythms could be a more suitable approach that needs less repetitions and, therefore, does not demand long attention spans. Since N170 has been associated with theta oscillations in response to gaze stimuli in adults, and theta band associated with attention to social stimuli and emotional arousal in infants and adults, analysing it in the context of exposition to direct and averted gaze stimuli in autistic children could be useful in the exploration of the underlying mechanisms behind reduced eye contact in autism. Hence, the aim of this work was to explore changes in theta rhythm at electrodes associated with evoked N170 component (P7 and P8) in response to dynamic shifts from gaze down to direct or averted gaze stimuli in 4–8-year-old children with and without autism (ASD, n = 19; TD, n = 17). Each child was exposed to a maximum of 24 trials (12 averted and 12 direct) divided equally into 4 blocks presented in a counterbalanced order across participants while EEG signals were recorded. The signals were analysed through a time-frequency decomposition to investigate theta power changes to stimulus presentation compared to baseline for each group and gaze stimulus, followed by comparisons between groups for each electrode and gaze stimulus. Results showed stronger changes on theta power at electrode P8 with significantly higher activity for the autism group compared to typically developing group for both shift to direct gaze and shift to averted gaze stimuli. It may be that children on the spectrum showed increased theta as a compensation strategy to process the stimuli, since both averted and direct gaze are socially relevant cues. Due to the limitations of the present work, further research is needed to determine the meaning of these results.
Keywords: autism spectrum disorder, theta rhythm, direct gaze, eye contact